Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1055/s-0031-1275724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Orchidopexy with or without Opening the External Oblique Fascia in Children with Superficial Inguinal Undescended Testis

Abstract: When investigating the surgical management of undescended testes, our study found differences in medial thigh sensory loss rate and procedure duration between the open and closed techniques. Operative treatment of UDT without opening the external oblique fascia is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…42 In comparison to standard inguinal orchidopexy, recent evidence from observational studies has suggested that the scrotal approach has equivalent success rates and complications, with advantage of a significantly shorter operative time. 38,39,43 At least two randomized, controlled trials comparing the two techniques (inguinal vs. scrotal) have been attempted and essentially confirmed those findings; 44,45 however, in one of the studies the authors also report mean length of stay above two days for both procedures, which questions the generalizability of the conclusions to our environment, where these procedures are almost universally undertaken on an outpatient basis. 44 Furthermore, none of these randomized, controlled trials prespecified the minimal clinically important difference in operative time to justify sample size calculation; therefore, their conclusions should be interpreted with caution.…”
Section: Scrotal Orchidopexymentioning
confidence: 96%
“…42 In comparison to standard inguinal orchidopexy, recent evidence from observational studies has suggested that the scrotal approach has equivalent success rates and complications, with advantage of a significantly shorter operative time. 38,39,43 At least two randomized, controlled trials comparing the two techniques (inguinal vs. scrotal) have been attempted and essentially confirmed those findings; 44,45 however, in one of the studies the authors also report mean length of stay above two days for both procedures, which questions the generalizability of the conclusions to our environment, where these procedures are almost universally undertaken on an outpatient basis. 44 Furthermore, none of these randomized, controlled trials prespecified the minimal clinically important difference in operative time to justify sample size calculation; therefore, their conclusions should be interpreted with caution.…”
Section: Scrotal Orchidopexymentioning
confidence: 96%
“…Four studies were judged good quality, 27,45,49,52 1 fair quality, 32 and the remainder poor quality. [28][29][30][31][33][34][35][36][37][38][39][40][42][43][44][46][47][48]50,51,53 Eleven studies reported outcomes after either 1-stage FS orchiopexy, 2-stage FS orchiopexy, or primary orchiopexy. [36][37][38][39][40][42][43][44][45]47,48 Nine of these studies, all retrospective cohorts, provided success rates by surgical procedure, although the choice of surgical method is made clinically and not with the intent of comparative effectiveness.…”
Section: Effectiveness Of Surgical Proceduresmentioning
confidence: 99%